PENGARUH RESIKO KREDIT MACET TERHADAP PROFITABILITAS PADA PT. ADIRA MULTIFINANCE - Willy Nurzaman; Dian Candra Fatihah (EKBIS (Ekonomi & Bisnis), 2021)
This study aims to determine how much influence bad loans have on profitability at PT. Adira Multi Finance baleendah bandung branch. The data collection method was carried out by interview techniques and data collection with the subject of financial reports at PT. Adira Multi Finance. Based on the results of the study, it was found that bad loans had an effect on Return On Assets, this was shown by the magnitude of the profitability value (p) = 0.007 which was smaller than 0.05 and t count was 6.476 which was greater than t table of 3.182. This means that bad credit has an effect on Return On Assets. So every time there is an increase in bad loans of Rp. 1,- then the Return On Assets will increase by 0.798. If bad credit occurs, the profit obtained from the financing of assets will decrease and this means that the occurrence of bad credit affects ROA. And also shown by the results of the magnitude of the value of profitability (p) = 0.010 which is less than 0.05 and t count of 5.919 which is smaller than t table of 3.182. This means that bad credit has an effect on Return On Equity. So every time there is an increase in bad loans of Rp. 1,- then Return On Equity will increase by 6.076. If bad credit occurs, the bank will take funds from reserves to eliminate bad loans, these reserves are obtained from profits, and profits are part of the bank's equity. Therefore, the existence of bad credit will affect ROE related to the rate of return on bank capital. The solution suggested to the company, namely a decrease in the quality of productive assets, should receive serious attention. This can be improved through an analysis of various conditions that occur and appropriate policies related to the quality of productive assets, liquidity, and the ability of banks to generate profits.